Cover Image. (11th July 2021) - Semenzato, Paola; Cagnacci, Francesca; Ossi, Federico; Eccel, Emanuele; Morellet, Nicolas; Hewison, A. J. Mark; Sturaro, Enrico; Ramanzin, Maurizio
Abstract : The cover image is based on the Letter Behavioural heat‐stress compensation in a cold‐adapted ungulate: Forage‐mediated responses to warming Alpine summers by Paola Semenzato et al., https://doi.org/10.1111/ele.13750 .